2016
DOI: 10.1016/j.ijcha.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact and evolution of right ventricular dysfunction after successful MitraClip implantation in patients with functional mitral regurgitation

Abstract: BackgroundRight ventricular dysfunction (RVdysf) is a predictor of poor outcome in patients with heart failure and valvular disease. The aim of this study was to evaluate the evolution and the impact of RVdysf in patients with moderate–severe functional mitral regurgitation (FMR) successfully treated with MitraClip.Methods and resultsFrom October 2008 to July 2014, 60 consecutive high surgical risk FMR patients were evaluated and stratified into two groups: RVdysf group (TAPSE < 16 mm and/or S′TDI < 10 cm/s, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…This observation is in line with our findings, and moreover, we found an improved RV-EF immediately after the PMVR procedure in patients with reduced RV-EF at baseline. It has been shown previously that echocardiography-derived 2D parameters like TAPSE and tissue Doppler derived peak systolic velocity of the lateral tricuspid annulus can identify patients with an increased risk of cardiovascular mortality despite a successful PMVR procedure [[25], [26], [27], [28]]. In our rather small patient collective, 12.5% of the patients with reduced RV-EF below 35% have died, whereas in the group of patients with RV-EF above 35%, 23.81% had died within 6 months after the PMVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with our findings, and moreover, we found an improved RV-EF immediately after the PMVR procedure in patients with reduced RV-EF at baseline. It has been shown previously that echocardiography-derived 2D parameters like TAPSE and tissue Doppler derived peak systolic velocity of the lateral tricuspid annulus can identify patients with an increased risk of cardiovascular mortality despite a successful PMVR procedure [[25], [26], [27], [28]]. In our rather small patient collective, 12.5% of the patients with reduced RV-EF below 35% have died, whereas in the group of patients with RV-EF above 35%, 23.81% had died within 6 months after the PMVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“….042). Conversely, Godino P 5 and colleagues 58 reported that successful Mitra-Clip procedure leads to a significant improvement of RV function even in patients with baseline RV dysfunction (TAPSE <16 mm and/or S' <10 cm/s). Reverse RV remodeling and reduced RV pressure overload by regression of MR and sPAP might explain its functional benefit.…”
Section: Right Ventricular Function and Mitral Regurgitationmentioning
confidence: 99%
“…In a small study including 60 patients with high-risk functional MR undergoing MitraClip, moderate and severe RV dysfunction (TAPSE <16 mm and S' <10 cm/s) was noticed in 37% of cases. 58 RV dysfunction results from complex hemodynamic and structural changes. Downstream, chronic MR leads to LV volume overload with subsequent LV enlargement and a decrease of interventricular septal function, and upstream, induces an increase in LA pressure and with a subsequent increase in sPAP and PCWP.…”
Section: Right Ventricular Function and Mitral Regurgitationmentioning
confidence: 99%
“…Importantly, TMVr treatment is capable of improving RV function. One study found an improvement of tricuspid annular plane excursion by 4 mm and peak systolic velocity by 4 cm/s at 6 months follow up [73] .…”
Section: Smr Only Collectivementioning
confidence: 99%